Answer:
y = ln( x + 6 ) - 11
h = 6
k = -11
h + k = -5
Explanation:
Horizontal shift changes whats inside the brackets, in other words, changes just the x-value.If the shift is right, the number should be subtracted, if the shift is left, the number should be added.
Vertical shift changes the equation as a whole.if the shift is up, the number of should be added.If the shift is down, the number should be subtracted.
The changes given to us are 3 units left ( horizontal translation ) and 5 units down ( vertical translation )
If we rewrite the equation, we have:
y = ln( x + 3 + 3 ) - 6 - 5
y = ln( x + 6 ) - 11